Interdisciplinary cooperation in the outpatient practice: results from a focus group interview with occupational therapists, speech and language therapists and physiotherapists / Gestaltung der interdisziplinären Zusammenarbeit in der ambulanten Therapie: Resultate eines Fokusgruppeninterviews mit Ergotherapeut*innen, Logopäd*innen und Physiotherapeut*innen - Malmendier Maischa; Klas Teresa; Lücking Christiane (Sciendo, 2024)
The complexity and diversity of healthcare conditions, as well as the financial and personnel challenges requires effective interdisciplinary collaboration (IDC) among various healthcare professionals (Robert-Bosch-Stiftung, 2011; Robert Koch Institute, 2015). In contrast to the inpatient practice, IDC has not established yet in primary care settings. There is a lack of concrete solutions that illustrate how IDC can be implemented in outpatient practice (Schmitz, Atzeni & Berchtold, 2020).